The Educational Context of a Literary Text: Some Notes on Marginalia and Drawings as Found on Material Containing The Teaching of Khety - Jurjens, Judith.
This article presents an analysis of two paratextual features which are occasionally found on material objects (ostraca and papyri) containing The Teaching of Khety, namely drawings and marginalia, in other words, hieratic signs written in the margin representing writing exercises or corrections. Inspired by Material Philology, the various examples are discussed in order to gain insights into the scribal environment in which Khety was produced. The paper focuses especially on the educational context of this literary text.